ELEMENTAL AND NON-ELEMENT FEATURES OF an INTERNATIONAL BOrder DISPUTE - Marsel Garaev (Электронное приложение к Российскому юридическому журналу, 2019)
The article is devoted to the legal essence, specificity and significance of international border disputes. The main scientific method of legal characteristics of an international border dispute is the structuring of its elemental and non-element features. The specifics of the international border dispute is manifested in its subject, object and the parties to a dispute (elemental features) as well as in a system of legal regulators, international legal instruments of exercising rights and obligations by the parties to a dispute, international legal instruments of peaceful settlement of a dispute, a complex of special legal procedures, certain legal consequences and a mechanism of legal regulation (non-element features). The interrelation and interdependence of elemental and non-elemental features of the international border dispute is revealed. The author indicates the problem of ensuring the balance of interests of the parties to a border dispute and notes the role of the International Court of Justice in the mechanism of dispute prevention. It is concluded that the international border dispute is a complex poly-compound phenomenon in international law, organically connected with various structural divisions of international law. A scientific and methodological value of identifying the elemental and non-elemental features of different international legal phenomena is demonstrated